Problematika Sampah Visual Media Luar Ruang: Tinjauan Regulasi Kampanye Pemilu dan Pilkada - Azka Abdi Amrurobbi (Badan Pengawas Pemilihan Umum, 2021)
Campaigning is a ritual that cannot be eliminated in implementing the General Election or Local Election. Given that campaigns are an essential part of political communication carried out by legislative or executive candidates to attract people's votes. Some of the campaign models that are frequently used are posters, banners, billboards, etc. This study uses a qualitative method by combining two data collection methods: observation and literature study. The results of this study are: First, conventional campaigns using posters, banners, billboards, and so on will create visual waste that disturbs beauty and the environment. Second, although the Perbawaslu already exists, the regulation has not created obedience in the implementation of campaigns carried out by candidates. But on the other hand, there is a Law on Environmental Protection and Management (UUPPLH) that exclusively regulates the use of criminal law facilities and administrative and civil law facilities related to environmental management. Therefore, it is necessary to make stricter regulations to create environmental order due to the implementation of the campaign. Third, conventional campaigns that create visual waste should be replaced with new media campaigns or campaigns using environmentally friendly materials. It aims to develop green elections.